Natural Products: Therapeutic Properties and Beyond II - Duarte, Ana Paula; Luís, Ângelo; Gallardo, Eugenia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Bioactive compounds have a range of chemical structures and biological activities. Recently, new advances regarding natural compounds were achieved, leading to their application in several areas related to human therapies. New computational methods that analyze the pharmacological potential of natural products have led to its its conversion into low toxicity molecules. This Special Issue has collected the most recent innovations in scientific research on natural products, together with the application of bioactive compounds in human health. It acts as a reference for academic researchers and health and industry professionals, particularly those working in the fields of medicinal chemistry, toxicology, phytochemistry, and natural product chemistry.